Effects of low-molecular-weight heparin and unfractionated heparin on patients with exertional heat stroke with thrombocytopenia: A prospective study - Li Cheng; Eric Allen Klomparens; De Lin Liu; Min Na Wang; Xiao Xue Yin; Wei Liu; Yuan Liu; Qi Feng Zhang; Gang Ye (Wolters Kluwer Medknow Publications, 2019)
Background: Thrombocytopenia often occurs in patients with exertional heat stroke (EHS). We aimed to investigate the effect of low-molecular-weight heparin sodium (LMWH) and unfractionated heparin (UFH) on coagulation and prognosis in the treatment of EHS with thrombocytopenia. Methods: In a prospective cohort study, 64 patients admitted to the emergent intensive care unit (ICU) were studied between July 2015 and October 2018. Patients were randomized to receive LMWH or UFH. Thirty-three patients were given LMWH 4000 IU twice a day for 5 days, by subcutaneous injection. Thirty-one patients were given UFH 5-10 U/kg × h for 5 days, by 24-h continuous intravenous infusion. Demographic and clinical data (platelets [PLTs] counts, activated partial thromboplastin time [aPTT], prothrombin time [PT], fibrinogen [FIB], D-dimer, presence of diffuse intravascular coagulation [DIC]), and mortality in the ICU were recorded along with the 28-day survival rate. The acute physiology and chronic health evaluation (APACHE) II score was calculated within 24 h of admission and used to indicate the severity of disease. Results: There were no significant differences in sex, age, APACHE II score, and core temperature between the two groups (P > 0.05). PLT and FIB were significantly increased after treatment in both groups (P < 0.05), while aPTT, PT, and D-dimer were significantly decreased after treatment in both groups (P < 0.05). No significant differences between the two groups were found in the incidence of DIC or ICU mortality (P > 0.05), but the incidence of bleeding in the LMWH group was significantly lower than in the UFH group (P < 0.05). There was not a significant difference in the 28-day survival rate between the two groups (P > 0.05). Conclusions: The results of this study support that the efficacy of LMWH and UFH in the prevention of thrombosis is equivalent. However, the incidence of bleeding was lower in LMWH group. LMWH and UFH had statistically similar rates of ICU mortality, 28-day mortality, and incidence of DIC. Our results suggest that LMWH may be safer than UFH for use in patients with EHS with thrombocytopenia.